Estudo dos ciclos biogeoquímicos por meio de uma abordagem de ensino por investigação contextualizada no cultivo em consórcio - Cunha, Denn Sidney Zacarias da (2022)
The understanding and appropriation of knowledge about the biogeochemical cycles addressed during high school faces the lack of a student base, especially in Chemistry. Understanding biogeochemical cycles implies recognizing the elements that compose/form organic matter (living beings), their renewal, assimilation or disposition and the interdependence between them, thus constituting a cycle. In addition, it is difficult for students to recognize that metabolic processes (aerobic respiration, fermentation, photosyn-thesis, and chemosynthesis) are ways of recycling matter developed by different life forms. To address these difficulties in teaching this subject, we developed a hybrid research strategy (remote and face-to-face), contextualizing the biogeochemical cycles of intercropping, with a view to promoting greater student involvement in learning this subject. The research was carried out at the Ideal College and Course, in Santo Antônio, Rio Grande do Norte, in which about 22% of the students live in rural areas, living directly with social and environmental problems related to the countryside, directed to 2nd graders, high school series. As qualitative research, we followed the participant research methodology and the data was obtained from the responses to the questionnaires and from the content analysis of the records of the arguments during the synchronous or face-to-face meetings. The work was organized in 3 stages, totaling six classes of 50 minutes each. In the initial interaction, remotely, the students answered a questionnaire in order to gather information about their previous knowledge about biogeochemical cycles and cultivation in a family farming consortium, which was reapplied at the end of the work. In the second and third stages, students were invited to carry out a set of activities/challenges on biogeochemical cycles in the context of corn/bean intercropping, developing argumentative-explanatory answer and, subsequently, consulting systematized information in the textbook in scientific articles and specialized videos, confronting them with their initial argumentative-explanatory answer. Finally, they presented and discussed their findings and the conclusions they reached as a group. We obtained a total of 34 answers in the questionnaires. In the arguments constructed for the argumentative-explanatory answer of the problematization in question, through the analysis of Toulmin's Argumentation Pattern, we identified that the justifications and supports/supports were present, being able to consider that the produced arguments have good quality, and some are more improved. than others depending on the combination of components. The Scientific Literacy indicators were analyzed in the proposed arguments and activities, together with the integration of the CTSA. It was still possible to observe the participation of the students with the proposed activities and the gain in the resulting/consequent argumentation of the understanding of the phenomena.